2013
DOI: 10.1126/scisignal.2004373
|View full text |Cite
|
Sign up to set email alerts
|

The ζ Isoform of Diacylglycerol Kinase Plays a Predominant Role in Regulatory T Cell Development and TCR-Mediated Ras Signaling

Abstract: Diacylglycerol (DAG) is a critical second messenger that mediates T cell receptor (TCR)–stimulated signaling. The abundance of DAG is reduced by the diacylglycerol kinases (DGKs), which catalyze the conversion of DAG to phosphatidic acid (PA) and thus inhibit DAG-mediated signaling. In T cells, the predominant DGK isoforms are DGKα and DGKζ, and deletion of the genes encoding either isoform enhances DAG-mediated signaling. We found that DGKζ, but not DGKα, suppressed the development of natural regulatory T (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 45 publications
2
69
1
Order By: Relevance
“…3). Several reports also pointed to differences in Treg signaling architecture, such as a different involvement of PKC-Θ (18), DGKζ (19), SHIP (20), or Dlgh1 (21). Finally, there have been reports that signaling intensity downstream of TCR engagement is reduced in Treg relative to Tconv cells (22)(23)(24).…”
Section: Imbalanced Signal Transduction In Regulatory T Cells Expressmentioning
confidence: 99%
“…3). Several reports also pointed to differences in Treg signaling architecture, such as a different involvement of PKC-Θ (18), DGKζ (19), SHIP (20), or Dlgh1 (21). Finally, there have been reports that signaling intensity downstream of TCR engagement is reduced in Treg relative to Tconv cells (22)(23)(24).…”
Section: Imbalanced Signal Transduction In Regulatory T Cells Expressmentioning
confidence: 99%
“…Whereas initial analyses reported a similar hyperactive phenotype in T cells from DGKa-and DGKz-deficient mice, a study suggests a dominant role for DGKz in suppressing the Ras signaling pathway (45). The dominant role of DGKz does not extend to other pathways; for example, DGKa-and DGKz-deficient T cells show a similar increase in the PKCq-dependent phosphorylation of IkBa (Fig.…”
Section: Dgkz Is Functionally Coupled To Pkc and Rasgrp1 And Limits Tmentioning
confidence: 95%
“…Joshi et al (45) suggested that although DGKz is less abundant than DGKa in T cells, it has higher affinity for RasGRP1. This difference contrasts with a mathematical model that characterizes the RasGRP1 and SOS pathways as analog and digital determinants, respectively, in the regulation of Ras activation in T cells (46).…”
Section: Dgkz Is Functionally Coupled To Pkc and Rasgrp1 And Limits Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with this, a loss of DGKz results in enhanced T cell responsiveness [6], supporting the hypothesis that DAG levels are involved in setting thresholds for productive T cell activation. Curiously, DGKz prevents the development of T regs within the thymus, demonstrating that this DGK plays a pivotal role in the balance between inflammation and immune tolerance [7]. The balance between inflammation and tolerance is obviously important for the prevention of autoimmunity and allograft rejection, but recent focus on the tumor microenvironment has led to the revelation that tumors evade immune clearance by tipping this balance toward tolerance.…”
mentioning
confidence: 99%